Improving Student Learning Outcomes By Modifying Baseball Props In The Shot Put Learning - Purnomo, Ariyanto Dwi; La Kamadi; Sofyan Haeruddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
Research on the use of baseball as a modified prop in the shot put material aims to make it easier for students to practice shot put at MI Nurul Hidayah Patemon. The data collection method used is the questionnaire or questionnaire method. The data analysis technique used is descriptive quantitative data analysis. Based on the results of research data processing which shows an increase in the percentage of the average score of fourth-grade students' learning motivation, which is 75.35% in the first cycle and increases to 88.25% in the second cycle, and has met the success criteria of this study, namely 80%. Based on the results of the study, it was concluded that the modification of teaching aids with baseball in the learning of shot put material could increase the learning spirit of the fourth-grade students of MI Nurul Hidayah Patemon in the Odd Semester of the 2021–2022 Academic Year.